Expanding the reach of vaccinology training in Africa: leveraging the success of the Annual African Vaccinology Course - Manga, Nayna; Amponsah-Dacosta, Edina; Hussey, Gregory; Muloiwa, Rudzani; Kagina, Benjamin M. (Frontiers in Health Services, 2023)
Introduction It is estimated that one in five African children lack access to recommended life-saving vaccines. This situation has been exacerbated by the COVID-19 pandemic which disrupted routine immunization services in several parts of the region. To better support recovery efforts and get immunization programmes back on track, policy makers, programme managers, immunization providers and academics need continuous upskilling. Unfortunately, the vaccinology training needed by these cadres remains limited and oftentimes inaccessible within our context. In addition, cadres should be continuously updated on advances in vaccinology so as to keep abreast with this rapidly evolving field. This calls for new and accessible approaches to training vaccinologists in Africa where the demand is high. Methods The aim of this proof-of-concept study was to ascertain the training needs of alumni of the Annual African Vaccinology Course and assess the effectiveness of an online webinar series in meeting those needs. Results We found that alumni from across Africa required refresher training to gain up-to-date information about new developments in vaccinology, leverage opportunities to reinforce and consolidate their knowledge, and exchange country-specific experiences with their counterparts. A prominent motivation for refresher training was the rapid developments and challenges brought on by the COVID-19 pandemic. Drawing on the expressed needs of our alumni, we developed a webinar training series. This series aimed to provide participants with training on current and emerging trends in vaccinology with a focus on the regional context. Online participation in the webinar series was found to be comparable to previous in-person training, reaching a diverse group of cadres, and allowing for participation of a richer global faculty due to fewer cost constraints. Further to this, a post-training survey indicated that generally, alumni training needs were successfully met. Discussion The findings suggest that an online approach can be used to expand the reach of vaccinology training in Africa.